The Impact of Human Capital Investment on Total Factor Productivity (TFP) Growth in 11 Countries - Phang, Kae Wen (Universiti Malaysia Sarawak, (UNIMAS), 2022)
The purpose of this study is to identify the impact of human capital investment especially the education investment and healthcare expenditure on the total factor productivity growth in 11 ASEAN countries including Armenia, Azerbaijan, Georgia, Indonesia, Iran, Lebanon, Malaysia, Myanmar, Peru, Singapore, and Thailand from 2010 to 2019. The research method used is panel data analysis which apply three models including Pooled Ordinary Least Squares, Fixed Effects Model, and Random Effects Model. The result shows that both education investment and healthcare expenditure positively impact total factor productivity, but the impact of education investment is not significant. The government could improve the impact of education investment by focusing more on the higher education level such as degree, master and doctoral level which promote technical efficiency and technological change.